Building ports with China's assistance: Perspectives from littoral countries. (2nd January 2018) - Liu, Peng; Pandit, Priyanka
ABSTRACT: China's port development projects at home and abroad has generated much discussion among the scholars and policymakers. Since 5 of the top 10 container ports in the world are in mainland China and its shipping companies carry more cargo than those of any other nation, it points to the port efficiency and maritime infrastructure that China has developed in the recent years. However, some of China's port development activities abroad have been subject of controversy pertaining to its intentions around these projects. In this backdrop, the paper seeks to analyse China's port development initiatives from littoral countries' perspective, given their critical dependence on ports such that the level of port efficiency affects the economic growth of the region. The study takes Bangladesh's port development projects as an example to indicate the opportunities and challenges involved in such initiatives and the need to continue with port development program in a win-win cooperative framework.